The unstoppable human species the emergence of homo sapiens in prehistory - Shea, John 1960- (Cambridge University Press, 2023)
In The Unstoppable Species John Shea explains how the earliest humans achieved mastery over all but the most severe, biosphere-level, extinction threats. He explores how and why we humans owe our survival skills to our global geographic range, a diaspora that was achieved during prehistoric times. By developing and integrating a suite of Ancestral Survival Skills, humans overcame survival challenges better than other hominins, and settled in previously unoccupied habitats. But how did they do it? How did early humans endure long enough to become our ancestors? Shea places 'how did they survive?' questions front and center in prehistory. Using an explicitly scientific, comparative, and hypothesis-testing approach, The Unstoppable Human Species critically examines much 'archaeological mythology' about prehistoric humans. Written in clear and engaging language, Shea's volume offers an original and thought-provoking perspective on human evolution. Moving beyond unproductive archaeological debates about prehistoric population movements, The Unstoppable Human Species generates new and interesting questions about human evolution
Title from publisher's bibliographic system (viewed on 16 Mar 2023)
Keywords: Human beings / Origin; Human evolution; Prehistoric peoples; Survival